2001
DOI: 10.1143/ptp.106.863
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Lines and Classical Solutions in Cubic Open String Field Theory

Abstract: We construct exact classical solutions in cubic open string field theory. By the redefinition of the string field, we find that the solutions correspond to finite deformations of the Wilson lines. The solutions have well-defined Fock space expressions, and they have no branch cut singularity of marginal parameters which was found in the analysis using level truncation approximation in Feynman-Siegel gauge. We also discuss marginal tachyon lump solutions at critical radius.Comment: 12 pages, LaTeX with PTPTeX.s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 12 publications
1
82
0
Order By: Relevance
“…We have shown that there exist exact solution of the open bosonic string field theory that describes any marginal deformation of the original configuration of N D0-branes localized in the origin of the space to the background configuration of N D0-branes in general positions. We have also seen that using the regulation of the solution, following [5,6,7] we have obtained solutions that is completely non singular. This fact can be used as an explanation of the presence of the singular term in the exact solution given in our previous work [14].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We have shown that there exist exact solution of the open bosonic string field theory that describes any marginal deformation of the original configuration of N D0-branes localized in the origin of the space to the background configuration of N D0-branes in general positions. We have also seen that using the regulation of the solution, following [5,6,7] we have obtained solutions that is completely non singular. This fact can be used as an explanation of the presence of the singular term in the exact solution given in our previous work [14].…”
Section: Resultsmentioning
confidence: 87%
“…However it is a pleasant duty for us mention some of the papers [5,6,7,8,9] that discuss related problems from different point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Since we will insert the operators on the middle point of the boundary, the following η = I(z) = − 1 z representation is useful: 9) which maps the middle point of the boundary to η = 0, as illustrated in figure (1). The star product of two projectors can be easily done inẑ representation.…”
Section: The Leading Order Solution For General Star Algebra Projectorsmentioning
confidence: 99%
“…14) 16) which have been at the heart of the manipulations in purely cubic string field theory [14]. Q L , Q R will be defined in section 4.…”
Section: Defining the 'Identity' String Fieldmentioning
confidence: 99%
“…But unfortunately, it has turned out that S 0 (a) is quite badly-behaved. For example, we have obtained 16 Q ǫ I δ , Q B Q ǫ I δ = −δ 2 sin 2 ǫ 1 2 tan ǫ 2 2 δ + tan ǫ 2…”
Section: D25-brane Tensionmentioning
confidence: 99%